Approaches to the surgical treatment of congenital clubfoot in children - A.F. Levitsky; A.V. Karabenyuk; A.A. Golubenko (Zaslavsky O.Yu., 2019)
Background. The clubfoot is a severe deformity of the foot. The birth rate of children with congenital clubfoot is 0.1-0.4 %. Since the end of the 1980s, when the technique of I. Ponseti gained worldwide recognition, early conservative treatment using staged plaster casts has been the main feature. The effectiveness of this technique reaches 93 % and can significantly reduce the number of surgical interventions. However, delayed treatment, the absence or non-compliance with the mode of wearing braces, concomitant neurological pathology lead to a decrease in the effectiveness of conservative treatment and the use of surgery. The objective of the study is a retrospective analysis of the results of applying our surgical method for congenital clubfoot in children. Materials and methods. From 2009 to 2017, 87 children (57 boys (78 feet) and 30 girls (37 feet)) with congenital clubfoot were treated surgically in the orthopaedics and trauma unit of National Children Specialized Hospital "OHMATDYT". During the study, we have taken into account the age, sex, type of deformity, volume of surgical intervention, immediate results of surgical treatment (up to 1 year), frequency of relapses. Sixty seven patients (83 feet) were operated for the first time, and in 20 children (32 feet), surgical treatment was repeated. The average age of patients was 4.5 years. Results. The immediate results of treatment (1 year after the operation) were good in 65 patients (74.7 %), satisfactory - in 14 (16 %) and unsatisfactory - in 8 (9.3 %). Two (2.3 %) patients had elements of excessive correction of deformity, which was manifested by pronation with valgus deformity of the heel. Relapses manifested by the appearance of one of deformity elements were detected in 8 (9.2 %) cases. The main their causes were non-compliance with the recommendations at the stages of rehabilitation (6 patients) and postoperative complications (2 patients). Conclusions. Immediate results of treatment (1 year after surgery) indicate the correctness of our approach for surgical reconstruction of the foot in patients with clubfoot.